Facile synthesis and thermal performances of stearic acid/titania core/shell nanocapsules by sol-gel method - Latibari, S.T.; Mehrali, M.; Mahlia, T.M.I.; Afifi, A.B.M.; Akhiani, A.R.; Metselaar, H.S.C. (Elsevier, 2015)
In order to improve the thermal properties of PCMs (phase change materials), in this study, a new series of NEPCMs (nanoencapsulated phase change materials) were synthesized using a sol-gel method with SA (stearic acid) as the core and TiO2 (titania) as the shell material. The effects of the weight ratios of the SA/titania precursor TTIP (titanium tetraisopropoxide) on the morphology, thermal performance and thermal conductivity of the prepared nanocapsules are discussed. The experimental results indicate that the SA was encapsulated in spheres with minimum and maximum diameters of 583.4 and 946.4 nm, at encapsulation ratios between 30.36 and 64.76. The results indicated that there was no chemical interaction between the core and shell materials, SA and TiO2, which were compatible with each other under controlled synthesis conditions of pH 10. The NEPCMs with high mass ratios of SA/TTIP exhibited enhanced phase change properties and higher encapsulation efficiencies but lower thermal conductivities than NEPCMs with low mass ratios. Good thermal reliability and chemical stability of the NEPCMs were obtained by cycling the material through 2500 melting/solidifying cycles. In conclusion, the outstanding thermal stability and reliability of the prepared nanocapsules make these materials appropriate phase change materials for thermal energy storage applications. (C) 2015 Elsevier Ltd. All rights reserved.